Pandemic amnesia: the absence of pandemic prevention and preparedness in Indonesia’s 2024 presidential election - Antonio, Hana; Mahendradhata, Yodi (Frontiers in Public Health, 2025)
The COVID-19 pandemic exposed profound weaknesses in global and national capacities for pandemic preparedness, emphasizing the urgent need for robust public health policies. This manuscript examines Indonesia’s 2024 presidential election, where leading candidates largely neglected pandemic prevention and preparedness despite the enduring socio-economic and health impacts of COVID-19. This work highlights the critical need to embed pandemic preparedness into electoral platforms, national policies, and global health agendas. Kingdon’s three streams framework (problem-policy-politics) illustrates how elections shape the prioritization of preparedness through shifts in political will. Therefore, public health advocates must strategically influence electoral agendas by forming unified policy proposals, developing tools like candidate scorecards, and mobilizing community education. Making pandemic preparedness a central electoral issue ensures readiness for future health crises and strengthens systemic resilience.